Bacteriology of the Core of Adenoids in A group of Iraqi Patients Undergoing Adenoidectomy. - Al-Wattar, Wifaq M.; Hassan, Hussein M.; Abdullah, Eman F. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Upper air way obstruction secondary to chronically inflamed adenoid and / or tonsil is a common problem, in the presence of recurrent infection; tonsillectomy and or adenoidectomy are the most common surgery applied among pediatric population. Objective: The aim of this study was to assess the type of bacteria encountered with- in the core of the adenoid tissue at time of operation. Subject and Methods: During a period from Feb.2005 to May 2005, twenty two adenoid samples were removed by surgery ,and cross sectioned and sent for culture and sensitivity, at the department of ENT in Al-jerahat hospital for surgical specialties , most of the patients were under 10 year’s old. Results: This study showed that the bacteria isolated from the core of adenoid tissue were mostly part of bacterial flora of the upper respiratory tract, only 7 patients showed a growth of pathogenic bacteria; to which special sensitivity tests were performed to detect antibiotic sensitivity. Conclusion: The bacteria of the core of the adenoid were mostly composed of normal flora, and few of them were pathogenic and resistant to most ordinary antibiotics